Survival benefit of thermal ablation therapy for patients with stage II-III non-small cell lung cancer: A propensity-matched analysis - Yang, Wei-Yu; He, Yu; Hu, Qikang; Peng, Muyun; Zhang, Zhe; Xie, Shouzhi; Yu, Fenglei (Frontiers in Oncology, 2022)
Background Thermal ablation (TA) is considered a safe alternative to surgical resection for the treatment of non-small cell lung cancer (NSCLC). While previous studies have shown that TA is beneficial for stage I NSCLC patients, however, few have reported on TA efficacy in patients with stage II-III NSCLC. The current study investigated the impact of TA on the overall survival (OS) and cancer-specific survival (CSS) of patients with stage II-III NSCLC. Methods Data on patients with stage II-III NSCLC who did not undergo surgical resection between 2004 and 2015 were extracted from the Surveillance, Epidemiology, and End Results (SEER) database. Propensity score matching (PSM), Kaplan-Meier survival curves, and Cox regression were used for statistical analyses. Results A total of 57,959 stage II-III NSCLC patients who did not undergo surgical resection were included in this study, 261 of whom received TA. Overall, TA was associated with a longer OS (p = 0.035) and CSS (p = 0.005) than non-ablation. After 1:3 PSM, 252 patients receiving TA and 732 patients not receiving ablation were enrolled in the matched cohort. The OS (p = 0.047) and CSS (p = 0.029) remained higher in the TA group than in the non-ablation group after PSM. Cox regression analysis showed that age, sex, primary tumor site, pathological type, tumor size, radiotherapy, chemotherapy, and thermal ablation were independently associated with OS and CSS (p <0.05). Subgroup analysis found that the advantages of TA were more pronounced among individuals ≥70 years of age, with tumor size ≤3.0 cm, or who did not receive radiotherapy. Conclusion TA could be an effective alternative treatment for stage II-III NSCLC patients unsuitable for surgical resection, particularly those ≥70 years of age, with tumor size ≤3.0 cm, or who have not received radiotherapy.